BEHAVIORAL BIASES AND INVESTMENT DECISIONS AMONG MALE AND FEMALE RETAIL INVESTORS IN INDIA - Sowmya T S; Muralidhar S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
PURPOSE – Investment decisions are pivotal in shaping individuals’ financial well-being and long- term wealth accumulation. However, these decisions are not always made rationally and objectively. Instead, they are often influenced by various psychological factors, including cognitive biases and sociocultural factors, such as gender. Understanding the interplay between gender dynamics and cognitive biases in investment decision-making is crucial for devising effective strategies to enhance financial literacy, promote gender equality, and optimize investment outcomes. Hence, the purpose of this research is to confirm the variables influencing cognitive behavioral biases such as overconfidence bias, confirmation bias, representativeness bias and anchoring bias of male and female investors in their investment decisions. RESEARCH DESIGN – In the current research study, a sample of 400 responses was gathered with the help of questionnaires and retail investors in India were the respondents for the study. Cronbach’s Alpha as used to check the reliability of the data gathered and Confirmatory Factor Analysis (CFA) was used to confirm the variables for the study. FINDINGS – This research paper delivers a second-order CFA model that displays adequate fit for both genders, with some variances in factor loadings, variances, and residuals. This proposes that while the overall structure is dependable, there are gender-specific gradations or shades. ORIGINALITY/VALUE – The study of behavioral bias in decision-making is a dynamic field, with each research study yielding varying results. There are numerous scales available for measuring behavioral biases. The items and dimensions of behavioral biases are well-defined, leading the study to employ Confirmatory Factor Analysis (CFA) to validate the variables influencing behavioral biases in the context of investment decisions among both men and women. The findings of this research are intended to lay the groundwork for further large-scale research.